Endovascular Surgery of Cerebral Aneurysms - Lv, Xianli; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides recent progress of neuroendovascular surgery, which is a minimally invasive treatment of cerebral aneurysms. Great advances have been made in the techniques, devices and large randomized clinical trials showing striking therapeutic benefit for cerebral aneurysms. The treatment of cerebral aneurysms has also seen substantial evolution, increasing the number of aneurysms that can be treated successfully with minimally invasive therapy. In the 17 chapters, authors introduce the techniques, devices, device structures and therapeutic concepts. Attendings, fellows, residents, medical students or anyone interested in sharpening their diagnostic and therapeutic skill set will benefit from reading this text. This book will include many clinical cases and skills and clinical concepts, which will benefit professional /practitioner.
1 Pathophysiology of Cerebral Aneurysms -- 2 Aneurysmal SAH Induced Vasospasm - Pathogenesis & Management -- 3 History of Endovascular Surgery of Cerebral Aneurysms -- 4 Drugs in Neurovascular Intervention -- 5 Current devices and uses -- 6 Neuroendovascular Management of Wide-neck Bifurcation Aneurysms -- 7 Dual lumen balloon assisted coil embolization -- 8 Blood blister-like aneurysms: pathogenesis and endovascular treatment -- 9 Flow Diverter stents -- 10 The off-label use of Flow Diverter -- 11 Complications of aneurysm embolization and their management : Basic and practical considerations -- 12 Clipping in uncoilable aneurysms -- 13 Open Treatment of Cerebral Aneurysms in the Endovascular Age -- 14 Recent advances in cerebral aneurysms -- 15 Microsurgery of Cerebral Aneurysms not Amenable to Endovascular Therapy -- 16 Giant intracranial aneurysm: flow alteration Vs flow diversion -- 17 Training protocols for Neuroendovascular Surgery.
Keywords: Nervous system$1 (BSurgery.s; Neurosurgery; Intracranial Aneurysm -- surgery; Endovascular Procedures